All-inkjet-printed MoS2 field-effect transistors on paper for low-cost and flexible electronics; Applied Nanoscience; Vol. 10, iss. 9 - Jiang Zhi; Chen Long; Chen Jin-Ju; Wang Yan; Xu Zhao-quan; Sowade Enrico E.; Baumann Reinhard R. R.; Sheremet E. S. Evgeniya Sergeevna; Rodriguez (Rodriges) Contreras R. D. Raul David; Feng Zhesheng (2020, 2020)
Title screen